Development and test run of civil engineering schedule acceleration model through ant colony optimization - Wang, C.; Abdul-Rahman, H.; Chow, P.S. (Taylor & Francis, 2016)
The traditional scheduling tool Critical Path Method (CPM) exhibits limitations in computational insufficiency due to exhaustive enumeration. Ant Colony Optimization (ACO) was therefore applied as a metaheuristic inspired by the ants behavior in foraging activities. A model development team was formed among construction engineers, IT professionals, and Mathematicians to develop a schedule acceleration model by integrating ACO into CPM to ensure proper resources allocated on critical path. The developed model CSAM-ACO targets on schedule acceleration by allocating resources on the newly found critical path after two stages of computation. The trial run proved CSAM-ACO model more favorable compared with CPM.